ADAB IN LEARNING TOWARDS THE ATTITUDES AND LEARNING OUTCOMES OF EDUCATIONAL TECHNOLOGY PROGRAM STUDENTS: ADAB DALAM PEMBELAJARAN TERHADAP SIKAP DAN HASIL BELAJAR MAHASISWA PRODI TEKNOLOGI PENDIDIKAN - Nurhayati, Nurhayati (Educate : Jurnal Teknologi Pendidikan, 2024)
Adab in this context refers to the principles, ethics, social norms and etiquette applied during academic interactions. Manners in learning have potential problems: (1) incompatibility between learning etiquette and the use of technology, (2) the influence of attitudes towards the use of technology, (3) the influence of ethics in learning educational technology, (4) the impact on the quality of learning outcomes, (5) differences in attitudes and learning outcomes between students. On this basis, in-depth research is needed with the aim of investigating and determining corrective action so that the implementation of Etiquette in the Foundations of Educational Technology course on student attitudes and learning outcomes does not happen again. Next, innovation is needed in the form of; (1) development of educational technology ethics guidelines, (2) development of learning models that integrate manners and technology, (3) development of attitudes and ethics evaluation tools, (4) use of innovative technology in the learning process. This research uses descriptive quantitative methods, data is processed using descriptive - inferential statistical techniques through regression analysis. The population and research sample were all 24 students taking the Foundations of Educational Technology course. The results of the research can be presented: (1) Manners in learning the Foundations of Educational Technology with a strong category, namely 0.715 in forming attitudes, (2) Manners with a weak category, namely 0.292 for increasing learning outcomes (3) Attitudes with a weak category, namely 0.329 for increasing learning outcomes. In conclusion based on these data, further research is recommended to increase the Adab dimension and Attitude dimension so that Learning Outcomes increase. For future researchers, they can compare manners and attitudes, which is stronger in increasing learning outcomes.